Associations between adolescent experiences, parent experiences and HbA1c: results following two surveys based on the Norwegian Childhood Diabetes Registry (NCDR) - Oyvind Bjertnaes; Hilde Hestad Iversen; Torild Skrivarhaug (BMJ Open)
Objective The aim of the current study was to determine the association between the experiences of adolescents and their parents with paediatric diabetes care at hospital outpatient departments and the association between these experiences and the Hemoglobin A1c (HbA1c) levels of adolescents.Design Cross-sectional survey.Setting Paediatric diabetes care at hospital outpatient departments in Norway.Participants Parents of all outpatients registered in the Norwegian Childhood Diabetes Registry and patients in the same registry aged 12–17 years.Intervention 1399 parents participated in a national pilot survey and 335 patients aged 12–17 years from the four largest paediatric outpatient departments in Norway responded in another pilot study. 181 paired parental and patient questionnaires were analysed.Main outcome measures The correlations between single items, indicator scores and overall scores were explored, as was that between indicator scores and HbA1c levels.Results There was a moderate but significant correlation between the responses of the patients and parents. For 40 of the 42 associations the correlations were significant, ranging from 0.16 to 0.42. A weak but significant negative correlation was found between the indicator scores of parents and the HbA1c levels of the adolescents. The strongest correlations were between HbA1c level and nurse contact and organisation, both with a correlation coefficient of 0.21 (p<0.01). There was no significant correlation between HbA1c level and patient indicator scores.Conclusions These results highlight the need to obtain information from both parents and adolescents, and indicate that the views of adolescents are not always mirrored by their parents. Three of the seven parent experience indicators were significantly related to the HbA1c levels of adolescents, but replication in future research with larger sample sizes is warranted.